Mechanics ofintertextuality in the series TV historical (mekhtarAlthagafi) a modelseries: سلوان بهاء كاظم الموسوي (Al-Academy, 2016)
It was not coincidene that much talk about intertxtuality prescription phenomenon tzms the creative process but have directed their tracks beyond the litery taxs prior or contemporaneous as the mechanics of in tertexuality able to contain all the pattems of expression in literary texts and fee structures ofher text copable of understanding and in terpretaion especially as the phenomenon of in twrtexuality actually depends on the existence of Understanding and interpretation, especially as the phenomenon of intertextuality actually depends on the existence of systems indicative independent but carries processes rebuild text templates one way or another are included in the templates and visions of other intellectual, Mstmjh languages cultural which was earlier or contemporary in building fabric new script